2019
DOI: 10.2174/1568009618666181031153151
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of YY1 OPB Peptide for its Anticancer Activity

Abstract: Background: The oncoprotein binding (OPB) domain of Yin Yang 1 (YY1) consists of 26 amino acids between G201 and S226, and is involved in YY1 interaction with multiple oncogene products, including MDM2, AKT, EZH2 and E1A. Through the OPB domain, YY1 promotes the oncogenic or proliferative regulation of these oncoproteins in cancer cells. We previously demonstrated that a peptide with the OPB sequence blocked YY1-AKT interaction and inhibited breast cancer cell proliferation. Objective: In the current study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…Previous studies indicated that EZH2 was recruited by YY1 to the promoters of target genes [ 41 ]. We reported that the peptide derived from the OPB sequence could block YY1 binding to several oncoproteins [ 30 , 42 ]. Thus, to evaluate the activity of the YPB peptide, we also synthesized the FITC-TAT-3×Glycine-OPB peptide (hereafter designated as the OPB peptide) and an unfused FITC-TAT peptide (designated as the Cont peptide) as positive and negative controls, respectively ( Figure 2 A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies indicated that EZH2 was recruited by YY1 to the promoters of target genes [ 41 ]. We reported that the peptide derived from the OPB sequence could block YY1 binding to several oncoproteins [ 30 , 42 ]. Thus, to evaluate the activity of the YPB peptide, we also synthesized the FITC-TAT-3×Glycine-OPB peptide (hereafter designated as the OPB peptide) and an unfused FITC-TAT peptide (designated as the Cont peptide) as positive and negative controls, respectively ( Figure 2 A).…”
Section: Resultsmentioning
confidence: 99%
“…The OPB domain of YY1 is involved in binding to at least four oncoproteins, including EZH2, MDM2, AKT, and E1A [ 30 ]. We reported that synthetic peptides based on the OPB sequence could inhibit breast cancer cell proliferation, but their effects in a mouse model were not evaluated [ 30 , 42 ]. In the current study, we mapped the binding site of YY1 on EZH2 and identified the YPB domain consisting of 27 residues.…”
Section: Discussionmentioning
confidence: 99%
“…The C2H2 ZF structure was first discovered by Miller et al . in 1985 in the Xenopus laevis transcription factor TFIIIA . Many transcription factors, including SP1, GATA1, ZEB1, and YY1, utilize ZF domains to bind their target promoters .…”
mentioning
confidence: 99%
“…Among them, C2H2 (Cys2-His2) is a classical and the most common type with a consensus zincbinding sequence of X 2 -C-X 2,4 -C-X 12 -H-X 3-5 -H (X: any amino acid) [21]. The C2H2 ZF structure was first discovered by Miller et al in 1985 in the Xenopus laevis transcription factor TFIIIA [14]. Many transcription factors, including SP1, GATA1, ZEB1, and YY1, utilize ZF domains to bind their target promoters [20].…”
mentioning
confidence: 99%
See 1 more Smart Citation